Seasonal dynamics of the water relations and photochemical efficiency of Copaifera langsdorffii Desf. co-occurring in savanna and seasonal forest - Rodrigues, Angélica Lino [UNESP]; da Silva Bertholdi, Angelo Albano [UNESP]; Mantoan, Luís Paulo Benetti [UNESP]; Franco, Danilo Miralha [UNESP]; Habermann, Gustavo [UNESP]; de Almeida, Luiz Fernando Rolim [UNESP] (Springer Nature, 2019)
Seasonal dynamics can have important effects on vegetation structure and the physiological responses of species that co-occur in tropical savanna and seasonal forest. Few studies have revealed the physiological adjustments achieved by species that are widely distributed among diverse environments and occupying different physiognomies. We evaluated physiological parameters of Copaifera langsdorffii Desf. between periods in formations of seasonal forest and savanna in Southeast Brazil. Stomatal conductance (g s ), relative water content, leaf water potential (Ψ Wleaf ), and chlorophyll a fluorescence were evaluated throughout the course of a single year. In the dry season, C. langsdorffii exhibited partial isohydric behavior in the savanna and strict anisohydric behavior in the seasonal forest. Stomatal regulation in anisohydric plants can have a negative effect on the functioning of the photochemical apparatus. Thereby, the lower thermal dissipation increases the excitation of photosystems resulting in degradation of PSII proteins, which is associated with environmental stress. Poor control of water loss under conditions of high evaporative demand and low leaf water potential lead to lower photochemical efficiency in plants of C. langsdorffii in the seasonal forest than in the savanna.
Keywords: Drought; Leaf water relationships; Photochemistry; Photosynthesis; Rehydration; Seasonality